Facile Synthesis of Highly Aligned Multiwalled Carbon Nanotubes from Polymer Precursors. (14th April 2009) - Han, Catherine Y.; Xiao, Zhi-Li; Wang, H. Hau; Lin, Xiao-Min; Trasobares, Susana; Cook, Russell E.
Abstract : We report a facile one-step approach which involves no flammable gas, no catalyst, and no in situ polymerization for the preparation of well-aligned carbon nanotube array. A polymer precursor is placed on top of an anodized aluminum oxide (AAO) membrane containing regular nanopore arrays, and slow heating under Ar flow allows the molten polymer to wet the template through adhesive force. The polymer spread into the nanopores of the template to form polymer nanotubes. Upon carbonization the resulting multi-walled carbon nanotubes duplicate the nanopores morphology precisely. The process is demonstrated for 230, 50, and 20 nm pore membranes. The synthesized carbon nanotubes are characterized with scanning/transmission electron microscopies, Raman spectroscopy, and resistive measurements. Convenient functionalization of the nanotubes with this method is demonstrated through premixing CoPt nanoparticles in the polymer precursors.